354 Decreasing Blood Transfusions with a Multidisciplinary Intra-Operative Algorithm in Open Craniosynostosis Surgery. (April 2023) - Drapeau, Annie Isabelle; Valenti, Olivia; Khansa, Ibrahim; Pearson, Gregory; Alalade, Emmanuel; Smith, Ashley
Abstract : INTRODUCTION: Blood transfusions are common in craniosynostosis surgery. Lack of an intra-operative transfusion protocol is a known risk factor for increased transfusion in these surgeries. METHODS: Quality improvement methodology was used (Institute for Healthcare Improvement model). A multidisciplinary team proceeded with a survey of anesthesiology teams to evaluate readiness for change; creation of an intra-operative algorithm (guiding decision making, timing of measuring hemoglobin, administration of fluid resuscitation, and indications for blood transfusion); and integration of the algorithm into the surgery time out. No modifications were made regarding the type of general anesthesia and surgical technique (1 neurosurgeon, 2 plastic surgeons). Data collected: use of the intra-operative algorithm, administration of blood products, lowest hemoglobin recorded during admission, and other relevant surgical details. Minimally invasive surgeries were excluded. RESULTS: Eighty-two surgeries were included in three cohorts: baseline (2018, n = 6), project initiation (2019-2020, n = 44), and post-intervention (2021-2022, n = 32). After implementation, the algorithm was used in all cases. Transfusions given in stable patients with a hemoglobin >7.5 g/dL decreased from a baseline of 40.0% to 0% (p < 0.01). This improvement was demonstrated with a centerline shift on a statistical process control chart (Aggregate Point Rule). Overall transfusion rate decreased from a baseline of 100% to 59.4% post-intervention (p = 0.07). Those receiving a transfusion did not require more than 1 unit of packed red blood cells. No transfusions were required beyond post-operative day 1. CONCLUSIONS: Implementation of a multidisciplinary intra-operative transfusion algorithm for open craniosynostosis surgery led to meaningful decrease in blood transfusions. This was achieved without changing surgical technique or introducing complex adjuncts.